The Effect of Liraglutide on Epicardial Adipose Tissue in Type 2 Diabetes - Na Zhao; Xiaoying Wang; Yongbo Wang; Junjie Yao; Chunhong Shi; Jianling Du; Ran Bai (Journal of Diabetes Research)
Objective. To study the effect of liraglutide on the thickness of epicardial adipose tissue (EAT) in type 2 diabetes mellitus (T2DM) patients with abdominal obesity. Methods. Abdominal obesity T2DM patients with poor glycemic control were collected and treated with liraglutide. The changes of blood glucose, blood lipid, waist circumference, body mass index (BMI), and EAT thickness were compared after 3 months of treatment with liraglutide. Cardiac magnetic resonance imaging (MRI) was used to measure EAT thickness. Results. After 3 months of treatment with liraglutide, glycosylated hemoglobin (HbA1c) decreased from 9.81±1.46% to 6.94±1.29% (95%CI=2.14–3.59, p<0.001). The weight decreased from 91.67±16.29 kg to 87.29±16.43 kg (95%CI=2.97–5.79, p<0.001). Waist circumference before treatment was 103.69±9.14 cm, and after treatment was 96.42±8.42 cm (95%CI=5.04–9.50, p<0.001). Total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) were significantly lower than those before treatment. TC decreased from 5.34±1.05 mmol/L to 4.86±0.97 mmol/L (95%CI=0.15–0.82, p<0.001). TG was 1.89 (1.48-3.17) and then to 1.92±0.69 (p=0.03). LDL-C decreased from 3.39±0.84 mmol/L to 3.01±0.74 mmol/L (95%CI=0.17–0.59, p=0.001). HDL-C increased by 1.7% after treatment, with no significant difference (p=0.062). More importantly, the thickness of EAT decreased from 5.0 (5.0-7.0) mm to 3.95±1.43 mm (p<0.001) after liraglutide administered for 3 months. Conclusion. Liraglutide significantly reduces EAT thickness in T2DM with abdominal obesity, which provides theoretical support for the cardiovascular benefits of liraglutide.